2013
DOI: 10.1093/icvts/ivt398
|View full text |Cite
|
Sign up to set email alerts
|

The application of intraoperative transit time flow measurement to accurately assess anastomotic quality in sequential vein grafting

Abstract: In this study, we found that temporary reduction of graft flow during TTFM seemed to enhance the sensitivity of TTFM to less-than-critical anastomotic defects in a sequential graft and to improve the overall accuracy of the intraoperative assessment of anastomotic quality in sequential vein grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Detailed surgical procedures of OPCABG have been described previously. 8 The posterior descending artery (PDA) is preferred for revascularization when the RCA is the target vessel in CABG. All patients were operated on by the same surgeon and the decision to perform CE was mainly based on the results of the last coronary angiogram before the operation and intraoperative findings of the target coronary artery.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed surgical procedures of OPCABG have been described previously. 8 The posterior descending artery (PDA) is preferred for revascularization when the RCA is the target vessel in CABG. All patients were operated on by the same surgeon and the decision to perform CE was mainly based on the results of the last coronary angiogram before the operation and intraoperative findings of the target coronary artery.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed surgical procedures of OPCAB have been described in our previous study. 14 The left internal mammary artery (LIMA) and the saphenous vein were routinely harvested. The saphenous veins were mainly harvested from the calf by a conventional open technique by the same surgeon.…”
Section: Operation Techniquementioning
confidence: 99%
“…Flow pattern is predominantly diastolic in all grafts but is more marked in the left coronary system; because of a smaller right ventricular transmyocardial pressure gradient, there is a comparatively greater systolic flow component in grafts to the right coronary system [2]. A number of studies have reported the usefulness and efficacy of TTFM [10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Takami et al [12,13] described the usefulness of TTFM in the detection of intraoperative graft failure of several types of grafts.…”
Section: Ultrasound Technologymentioning
confidence: 99%